Porous Silicon Formation by Stain Etching on Pyramid Surface in U-Shape MSM Photodetector - Rangson Muanghlua; Narin Atiwongsangthong; Jidapa Vijafun; Kamonwan Suttijalern; Surasak Niemcharoen; Seangrawee Buakaew (My University, 2024)
In this paper, the porous silicon formation on pyramid surface in U-shape MSM photodetector was studied. Stain etching technique was used to prepare porous silicon material. The solution for stain etching contained the mixed solution of hydrofluoric acid (HF), nitric acid (HNO3) and deionized water (DI) with ratios 1: 3: 5 and used halogen lamp expouse 30,000 lux between etching for excite porous formation in 2 minutes. Porous silicon was fabricated on pyramid surface in U shape which between metal electrode titanium and aluminum on p-type silicon $20-25 \Omega-\mathrm{cm}$ to reduce the reflection of incident light and to increase a photocurrent of MSM photodetector. In the final part of this paper are the comparison physical morhhology and electrical characteristic of porous silicon on pyramid surface in U shape MSM photodetector with pyramid in U-shape MSM photodetector without porous silicon on the surface and planar MSM photodetector. The physical morphology of porous silicon on pyramid surface in U-shape was studied by using scanning electron microscopy (SEM). The electrical characteristic was investigated by using incident light with wave length 635 nm and power 6 mW at bias voltage 10 V. The result of comparison, we found that porous silicon on the surface of pyramid in U-shape MSM photodetector is rougher than pyramid in U-shape MSM photodetector without porous silicon on the surface. The electrical characteristic of porous silicon on pyramid surface in U-shape MSM photodetector respond incident light higher than pyramid in U-shape MSM photodetector without porous silicon on the surface. Therefore the forming porous silicon on the suface of pyramid in U-shape MSM photodetector is appropriate for the fabrication of MSM photodetector with high photocurrent.
Keywords: Silicon Nanostructures and Photoluminescence; Nanowire Synthesis and Applications; Thin-Film Transistor Technologies